Twenty-four-hour blood pressure management in India: A position statement by Indian College of cardiology - Jayagopal, P; Srinivas, B; Raghu, T; Khanna, N; Srinivas, K; Manchanda, S; Guha, Shantanu; Ray, Saumitra; Thomas, Joy; Srivastava, Sameer; Roy, Devanu; Shetty, Sadanand; et al. (Journal of Indian College of Cardiology, 2020)
Blood pressure (BP), even in healthy normotensive individuals, is dynamic, varies with a circadian periodicity, and is influenced by physiological and environmental factors. Abnormal 24-h BP patterns have been observed in many patients with hypertension (HTN), which may be overlooked if evaluations are based only on office BP measurements. Out of office BP measurements, such as Ambulatory Blood Pressure Monitoring and Home Blood Pressure Monitoring (ABPM and HBPM) is important for optimal BP management and are better predictors of adverse outcomes. However, HTN diagnosis and management are often based on relatively few clinic BP measurements, and there are no recommendations to guide clinicians managing patients with abnormal 24-h BP patterns in India. Thus, the present consensus statement aims to provide uniform evidence-based recommendations for the diagnosis and management of abnormal 24-h BP patterns. Strategies for screening for HTN based on the current prevalence trends in India have been suggested. Further, recommendations on the appropriate use of ABPM and HBPM in diagnosis and management of HTN are provided.